Mathematical models for conventional and microwave thermal deactivation of Enterococcus faecalis, Staphylococcus aureus and Escherichia coli - Benjamin, E.; Reznik, A.; Benjamin, E.; Williams, A.L. (Cellular and Molecular Biology, 2007)
Temperature dependencies of survival fecal coliforms such as Enterococcus faecalis, Staphylococcus aureus and Escherichia coli in water were investigated between 25 - 65deg C. Measured dependencies had "bell" shaped form with maximum bacterial viability at 35 - 45 degC. The rates of growth and decay of bacterial viability depend on specific forms of bacteria. At temperatures of 60 - 65 degC the number of viable bacteria decreased in one hundred times in comparison with the maximum value. Similar "bell" shape forms were found for dependencies between bacterial viability and time of microwave ( dielectric ) heating of water. The dependencies had maximum value at 1 - 2 min of microwave heating. Then, the number of viable bacteria decreased, and at 4 - 5 min of microwave heating, became insignificantly small. The proposed mathematical models for conventional and microwave heating took into account "growth" and "death" factors of bacteria, and had forms of second degree polynomial functions. The results showed good relationships ( with coefficient correlation 0.84 - 0.99 ) between the proposed mathematical models and experimental data for both conventional and microwave heating.